1980
DOI: 10.1128/aac.18.4.638
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal activity of cerumen

Abstract: Freshly collected cerumen (dry form) suspended at a concentration of 3% in glycerol-sodium bicarbonate buffer showed bactericidal activity against some strains of bacteria tested. This suspension reduced the viability of Haemophilus influenzae, Escherichia coli K-12, and Serratia marcescens by more than 99%, whereas the viability of two Pseudomonas aeruginosa isolates, E. coli K-1, Streptococcus, and two Staphylococcus aureus isolates of human origin was reduced by 30 to 80%. The results support the hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
4

Year Published

1982
1982
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 14 publications
(20 reference statements)
4
44
1
4
Order By: Relevance
“…It has been know since the 1940s that sebum lipids impart a self-disinfecting activity to the skin surface [1,2], and it has been accepted that free fatty acids are responsible for this property [2][3][4]. However, relatively little direct evidence has been published to support this claim or identify which fatty acids may be responsible.…”
Section: Introductionmentioning
confidence: 83%
“…It has been know since the 1940s that sebum lipids impart a self-disinfecting activity to the skin surface [1,2], and it has been accepted that free fatty acids are responsible for this property [2][3][4]. However, relatively little direct evidence has been published to support this claim or identify which fatty acids may be responsible.…”
Section: Introductionmentioning
confidence: 83%
“…Earlier studies suggested that the rich nutrients of cerumen support the growth of bacteria and fungi (Creed and Negus, 1926;Perry and Nichols, 1956;Singer et al, 1952;Syverton et al, 1946). On the other hand, cerumen suspended in buffer showed bactericidal activity against certain strains of common bacteria which are often encountered in humans (Chai and Chai, 1980). The reason of controversy could be that all studies have been made on cerumen in different forms (dry-form or/and wet-form) or using various extractive methods.…”
Section: Introductionmentioning
confidence: 96%
“…The argumentation against a bactericidal activity are based on the consideration that the rich nutrients of ear wax enable bacteria and fungi to grow [57][58][59][60][61]. On the other hand there are several reports describing an antimicrobial effect of ear wax with an effect against a wide range of bacteria including Haemophilus influenzae, Staphylococcus aureus, Escherichia coli and fungi [61][62][63][64][65][66]. Stoeckelhuber et al reported the detection of the antimicrobial proteins ß-defensin-1, ß-defensin-2, cathelicidin, lysozyme, lactoferrin, MUC1 and the secretory component of IgA in the ceruminous glandular cells by histochemical analysis [67].…”
Section: Discussionmentioning
confidence: 99%